Investigation of the Usability of Reduced Alkalinity Red Mud in the Building Material Industry - Miklós Jakab; Gergely Balázs Patthy; Tamás Korim; Éva Makó (Resources, 2023)
Untreated and pH-reduced red mud is used as a potential raw material in ceramic technology. During the alkalinity reduction process, CO2 is bubbled through the untreated red mud, which is particularly important as it can reduce the CO2 content of the atmosphere, and the pH of the red mud. Therefore, this method serves as a CO2 capture technique that utilizes waste as a raw material with low costs. Besides, reducing CO2 emission, it allows the production of material suitable for brick manufacturing from waste. In this study, treated and reduced alkalinity red mud was mixed with clay in the range of 5–30 wt%, and the physical, chemical, mechanical, and technologically important properties of the dried and sintered bricks were examined. The application of reduced alkalinity red mud as an additive offers advantages, as the resulting bricks require less water for processing, are less sensitive to drying, and their strength values exceed those of the commercially available bricks. Therefore, the technique presented in the study enables the production of bricks and roof tiles with advantageous properties using waste materials.